The Private Practicing Physician-Investigator: Ethical Implications of Clinical Research in the Office Setting - Klein, Jason E. (The Hastings Center report, 2002)
Drug companies are moving their research from academic medical centers to physicians’ private offices. The shift brings in more subjects, and could mean faster and better results. It also changes the physician's relationship to patients, dangles monetary lures in front of physicians, and could produce subjects who don't understand what they're participating in and results that are unreliable.